Answer:
4
_
3.14159265358979323846264338327952884197169393751
Answer:
Step-by-step explanation:
I assume that you mean
sec(x)-tan(x) = 1 / ( sec(x) + tan(x) ) , right ?
then this is equivalent to
[ sec(x) - tan(x) ] x [ sec(x) + tan(x) ] = 1
let s evaluate it, we got
sec2(x) - sec(x)tan(x) + - sec(x)tan(x) - tan2(x) = sec2(x) - tan2(x)
= (1 - sin2(x) ) / cos2(x) = cos2(x) / cos2(x) = 1
as cos2(x) + sin2(x) = 1
The answer would be -12+8i
2 students more were introducced in the class and each group had 8 people
Answer:
x=1 and y= 6
Step-by-step explanation:
and for y its a positive cause their both negitives